2016
DOI: 10.3892/mmr.2016.5549
|View full text |Cite
|
Sign up to set email alerts
|

Periodic mechanical stress induces the extracellular matrix expression and migration of rat nucleus pulposus cells by upregulating the expression of intergrin α1 and phosphorylation of downstream phospholipase Cγ1

Abstract: Intervertebral disk degeneration (IDD) is a major cause of low back pain and an important socioeconomic burden. Degradation of the extracellular matrix (ECM) of nucleus pulposus (NP) cells in the interverterbal disk is important for IDD. Stress of a suitable frequency and amplitude promotes the synthesis of the ECM of NP cells, however, the associated mechanisms remain to be fully elucidated The present study aimed to investigate the effect of integrin α1 on the migration and ECM synthesis of NP cells under so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 34 publications
(41 reference statements)
4
13
0
Order By: Relevance
“…Among the five KEGG pathways, the chemokine pathway was identified as being strongly associated with the development of IDD. Previous studies have confirmed that multiple molecules involved in these pathways were associated with pathological changes in that intervertebral disc tissue ( Gao et al, 2016 ; Wang J. et al, 2019 ; Liu et al, 2020 ). Our data mining results further confirm that the chemokine pathway plays a crucial role in the development of IDD.…”
Section: Discussionmentioning
confidence: 83%
“…Among the five KEGG pathways, the chemokine pathway was identified as being strongly associated with the development of IDD. Previous studies have confirmed that multiple molecules involved in these pathways were associated with pathological changes in that intervertebral disc tissue ( Gao et al, 2016 ; Wang J. et al, 2019 ; Liu et al, 2020 ). Our data mining results further confirm that the chemokine pathway plays a crucial role in the development of IDD.…”
Section: Discussionmentioning
confidence: 83%
“…Sorting decreased the abundance of the DG family members DG(44:12) (depleted in Ab+Sort), DG(36:5) (FC −1.52), DG(36:2) (FC −1.64), DG(38:5) (FC −1.59), DG(40:4) (FC −1.40), DG(42:8) (FC −1.60), DG(36:8) (FC −0.95), DG­(P-32:1) (depleted in Ab+Sort), DG(34:2) (FC −1.58), DG(36:4) (depleted in Ab+Sort), DG(38:7) (FC −1.39), DG(38:4) (FC −1.54), DG(40:7) (FC −1.48), DG(42:10) (FC −1.32), DG(40:3) (FC −1.18), and increased species DG(32:3) (appeared in Ab+Sort, when absent in Ctrl), DG(34:5) (FC 1.09 in Sort), altogether possibly reflecting PLC and DG lipase activity. PLC activity was previously found to depend upon periodic mechanical stress, electrostatic potential, and elastic stress of lipid membranes. The observed increase in DG consumption in FACS sorted macrophages might be associated with PLC and DG lipase activities, which are crucial in the biosynthesis of 2-arachidonoylglycerol (2-AG), , the AA precursor in the endocannabinoid signaling pathway . The outcome is an inflammatory-like status featuring increased energy consumption and cell damage, potentially compromising cell homeostasis.…”
Section: Results and Discussionmentioning
confidence: 96%
“…in Sort), altogether possibly reflecting PLC and DG lipase activity. PLC activity was previously found to depend upon periodic mechanical stress, electrostatic potential, and elastic stress of lipid membranes [39][40][41] . The observed increase in DG consumption in FACS sorted macrophages might be associated with PLC and DG lipase activities, which are crucial in the biosynthesis of 2-arachidonoylglycerol (2-AG) 42,43 , the AA precursor in the endocannabinoid signalling pathway 43 .…”
Section: Mechanosensitivity Translates Into Cell Stressmentioning
confidence: 99%
“…Introduction of an AM-3 tumour mass downregulated 30 genes and upregulated 1 gene in the osteoblasts. ALPL and bone development COL2A1 58 , were under-expressed by 5.5-fold (p = 0.003) and 4.2-fold (p = 0.01) respectively. A differentiation factor GDF10 was under-expressed by 17.8-fold (p = 0.0007), which indicated strong inhibition of osteoblast differentiation by AM-3 cells.…”
Section: Resultsmentioning
confidence: 99%